2023
DOI: 10.1002/bkcs.12715
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies on the dynamic heterogeneity of organic ionic plastic crystals

Abstract: Organic ionic plastic crystals (OIPCs) are one of promising solid‐state electrolytes (SSEs) for all‐solid‐state batteries. OIPCs consist of organic ions that form crystalline solid phases. It is a challenging but critical task in the development of SSEs to improve the ion conductivity of lithium ions in such crystalline solid phases. We discuss our recent simulation studies on the transport mechanism of ions in OIPCs and show that the dynamic heterogeneity should be a key to the transport mechanism. We aim to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…The Monte Carlo (MC) scheme tracks a system through probabilistic calculations using random sampling, 135 while MD simulations involve integrating Newton's equations of motion, enabling representation of the positions, velocities, and accelerations of particles as functions of time 136 . Both methods are widely used in simulations of soft matter systems, 137–142 and can be applied to biomolecular phase separation.…”
Section: How To Model Biomolecular Phase Separationmentioning
confidence: 99%
“…The Monte Carlo (MC) scheme tracks a system through probabilistic calculations using random sampling, 135 while MD simulations involve integrating Newton's equations of motion, enabling representation of the positions, velocities, and accelerations of particles as functions of time 136 . Both methods are widely used in simulations of soft matter systems, 137–142 and can be applied to biomolecular phase separation.…”
Section: How To Model Biomolecular Phase Separationmentioning
confidence: 99%
“…spherical-like or other). 29 Yunis et al have reported that OIPCs with symmetric cations were found to exhibit high ionic conductivity in their S1), the conductivity of the ethyl analogue is lower than that of t h e m e t h y l a n a l o g u e f o r t h e [ T F S A ] − ( b i s -(trifluoromethylsulfonyl)amide, see Figure S1) and BF 4…”
Section: ■ Introductionmentioning
confidence: 99%
“…Park et al have also employed MD simulations to reveal more about the structural factors involved in the PC phase for imidazolium cations of various structures, highlighting the effects of polarizability, and how this is influenced by ion size and shape (i.e. spherical-like or other) …”
Section: Introductionmentioning
confidence: 99%
“…spherical-like or other). 29 Pringle et al have reported that IPCs with symmetric cations were found to exhibit high ion conductivity in their study of N,N-diethylpyrrolidinium ([C2epyr] + , see Figure S1)-based IPCs with various anions, but the relationship between structure and performance is complex. Comparing [C2epyr] + with N-ethyl-N-methylpyrrolidinium ([C2mpyr] + , see Figure S1), the conductivity of the ethyl analogue is lower than that of the methyl analogue for the [TFSA] − (bis(trifluoromethylsulfonyl)amide, see Figure S1) and BF4 − (tetrafluoroborate, see Figure S1) salts, but conversely the [FSA] − anion leads to significantly higher conductivity for the ethyl analogue compared to the methyl analogue.…”
Section: Introductionmentioning
confidence: 99%